The Dynamics of Perceived Benefits, Risks, and Frequency of ChatGPT Use in Indonesian Students' Academic Writing - Hermawan, Dwi; Firnanda, Zekry Tri (Lia Center of Research and Education, 2025)
The rapid advancement of artificial intelligence (AI), especially LLMs like ChatGPT has changed students' school habits. It also highlights risks, such as copying and privacy concerns, that those who create rules must address. This research examines how students perceive the benefits and drawbacks of ChatGPT, as well as their frequency of use for school writing in Indonesia. We conducted a survey of 272 students from two government colleges, specifically targeting them. We changed some ideas from studies by Balraj (2025), Meyer et al (2024), Črček & Patekar (2023), and OECD (2023). We analyzed the data using basic statistics, the Pearson correlation test, and multiple linear regression. The results show that students use ChatGPT extensively for writing papers, creating summaries, understanding complex ideas, and correcting their grammar. They thought the good things were good (M = 4.08), mainly because they made them faster and helped them write better. However, they also worried about issues such as AI causing copying, being overly reliant on it, incorrect information, and privacy concerns (M = 3.81). Regression analysis revealed that exposure to the positive aspects of ChatGPT was associated with increased usage (β = 0.39, p < 0.001). These results underscore the need for clear rules to ensure the integrity of schoolwork and protect privacy with AI, prompting educators and policymakers to take a proactive role in shaping ethical guidelines.